2005
DOI: 10.2308/bria.2005.17.1.133
|View full text |Cite
|
Sign up to set email alerts
|

20-F Reconciliations and Investors' Perceptions of Risk, Financial Performance, and Quality of Accounting Principles

Abstract: This paper investigates whether the increases and decreases to earnings and stockholders' equity presented in 20-F reconciliations influence perceptions of the risk of investing, the quality of the accounting principles, and the financial performance of the reporting firm. The research results indicate that subjects perceive the risk of a hypothetical firm filing a 20-F reconciliation with reconciliation decreases to be higher, and the quality of accounting principles lower, than a hypothetical firm either com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…These results are consistent with the effects predicted by attribute framing theory (Levin and Gaeth, 1988;Levin, Gaeth and Schneider, 1998;Levin, et al, 2002) and provide important insights into the impact of 20-F reconciliations on investment recommendations by financial professionals. In a further extension of Maroney and Ó hÓgartaigh (2005), these findings are also consistent with recent research studies (see e.g., Bradshaw, 2004;Jegadeesh et al, 2004) that have found that analysts' recommendations are based more on heuristics than on economic analyses.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results are consistent with the effects predicted by attribute framing theory (Levin and Gaeth, 1988;Levin, Gaeth and Schneider, 1998;Levin, et al, 2002) and provide important insights into the impact of 20-F reconciliations on investment recommendations by financial professionals. In a further extension of Maroney and Ó hÓgartaigh (2005), these findings are also consistent with recent research studies (see e.g., Bradshaw, 2004;Jegadeesh et al, 2004) that have found that analysts' recommendations are based more on heuristics than on economic analyses.…”
Section: Introductionsupporting
confidence: 88%
“…Yates (1990) refers to framing as "variations in the presentation of a decision situation such that the decision maker constructs markedly different representations of that situation" (p. 361). Maroney and Ó hÓgartaigh (2005) find that the gains and losses represented in 20-F reconciliations differentially affect participants' (undergraduate and graduate accounting students) assessment of the quality of accounting principles and assessment of investment risk. Further, for participants most likely to invest in international stocks, assessments of financial performance were also lower in the case of reconciliation losses.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
See 2 more Smart Citations
“…The next question might be, ''what do you think this suggests about IFRS and US GAAP?' ' Maroney and Ó h Ó gartaigh (2005) found that when the reconciling items increased the reported income, investors perceived the non-US GAAP financial reporting principles to be of higher quality than when the reconciling items decreased reported income. The authors suggest that companies faced with incomedecreasing reconciling items may be better off filing their Form 20-F based upon US GAAP to avoid the negative framing issues associated with the reconciliation.…”
Section: In-class Discussion Topicsmentioning
confidence: 92%